FIGURE 24 in An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS "Challenger" expedition and deposited in the Natural History Museum, London - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
FIGURE 24. Teloscalpellum antarcticum (Hoek, 1883). "Challenger" Stn 153: holotype, left and right lateral view. Scale bar 10 mm. : Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS "Challenger" expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on page 37, DOI: 10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932